Memperbaiki Mampu Layan Material Pelindung Struktur Face Fender Jetty Dengan Spesifikasi Material Solid Rubber Fender - Sulardi, Sulardi (Universitas Borneo Tarakan, 2017)
Face fender structure jetty No.1 PT. Pertamina RU V is a Dutch building construction with a protective face fender structure of ulin wood material. The problem faced is the wood protective material ulin fragile, easily broken and can damage the hull when leaning. This study aims to provide a description of the specification of solid rubber fender material and its fitting method as a protective fender jetty structure No.1 PT. Pertamina RU V Balikpapan. The research method used is the application research method with case study approach handling the problem of damage to the protective material of the face fender jetty structure. The result of the research shows the material specification which suitable and suitable to be used as the substitute for the protective wood of face fender structure is the specification of solid rubber fender type V because it has high elasticity and elongation, impact and vibration reduction, not easily broken, not easy to break, according to SNI 06-3568-2006 standard, MOT standard (Japan) and according to EAU standard 1990 (Germany). The result of this research is succes story to overcome the problems in Pertamina RU V which can be replicated in Pertamina Other work units and outside Pertamina environment experiencing similar problems. Keywords: Ulin wood protector